Detection of RNA viruses in potato seed-tubers from northern Antioquia (Colombia) - García, Andrea; Giraldo, Susana; Higuita, Mónica; Hoyos, Rodrigo; Marín, Mauricio; Gutiérrez, Pablo (Revista Ceres, 2023)
The most important viruses infecting potato in Colombia are PVY, PLRV, PVS, PYVV, PVV, PVX, PMTV, and PVB. Unfortunately, recent investigations on the health status of uncertified and certified seed-tubers of Solanum tuberosum cv. Diacol Capiro and Solanum phureja cv. Criolla Colombia used by farmers in eastern Antioquia (Colombia) have revealed alarming levels of infection by these viruses in all types of seeds distributed in the region. A similar study on northern Antioquia, testing all these eight viruses has not been performed. To close this gap, we present a complementary study on the prevalence of viruses in seed-tubers distributed and commercialized in this region using a combination of RT-qPCR and high-throughput sequencing. Our results further confirm the poor quality of seed-tubers used in Colombia and suggests infection by tobacco necrosis virus D (TNV-D), which is the first report for this virus in Colombia.